Fully solution-processed metal oxide thin-film transistors via a low-temperature aqueous route. Issue 8 (1st June 2017) - Xu, Wangying; Long, Mingzhu; Zhang, Tiankai; Liang, Lingyan; Cao, Hongtao; Zhu, Deliang; Xu, Jian-Bin
Abstract: We report a facile and low-temperature aqueous route for the fabrication of various oxide thin films (Al2 O3, In2 O3 and InZnO). A detail study is carried out to reveal the formation and properties of these sol-gel-derived thin films. The results show that the water-based oxide thin films undergo the decomposition of nitrate group as well as conversion of metal hydroxides to form metal oxide framework. High quality oxide thin film could be achieved at low temperature by this aqueous route. Furthermore, these oxide thin films are integrated to form thin-film transistors (TFTs) and the electrical performance is systematically studied. In particular, we successfully demonstrate In2 O3 /Al2 O3 TFTs with high mobility of 30.88 cm 2  V −1 s −1 and low operation voltage of 4 V at a maximum processing temperature of 250 °C.